1962
DOI: 10.1084/jem.116.5.611
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Demonstration of the Reticuloendothelial Clearance of Circulating Fibrin Aggregates

Abstract: PLATES 83 AND 84(Received for publication, July 6, 1962) When thrombin is administered intravenously to rabbits for several hours at a rate just insufficient to produce intravascular thrombosis, there is nevertheless conversion of much of the animal's circulating fibrinogen to fibrin (1). In most instances, no detrimental effect is observed, and no extensive fibrin deposition is found (2). This absence of pathologic alterations in the face of extensive intravascular fibrin formation has generally been ascri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

1965
1965
1993
1993

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(22 citation statements)
references
References 8 publications
0
21
0
1
Order By: Relevance
“…Many of the agents used to provoke the generalized Shwartzman phenomenon accelerate coagulation (4)(5)(6)18). In in vitro studies (16)(17)(18), platelets are required for the demonstration of acceleration of eoagtflation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the agents used to provoke the generalized Shwartzman phenomenon accelerate coagulation (4)(5)(6)18). In in vitro studies (16)(17)(18), platelets are required for the demonstration of acceleration of eoagtflation.…”
Section: Discussionmentioning
confidence: 99%
“…Baltimore) PLATES 17 AND 18 (Received for publication, September 10, 1954) There are many indications that the effects of endotoxin upon blood vessels (1), leucocytes (2,3), and coagulation (4)(5) are important in production of the Shwartzman reaction. The effects of endotoxin upon blood vessels and leucocytes cannot be disputed, but involvement of platelets in the intravascular clotting of the Shwartzman phenomenon has never been established with certainty.…”
Section: (From the Department Of Medicine The Johns Hopkins Universimentioning
confidence: 99%
“…Previous investigations have shown that each injection of endotoxin activates the clotting mechanism. However, the first apparently produces only transient injury to the reticuloendothelial system (RES) so that clearance of circulating endotoxin [7], clotting intermediates [8], and fibrin [9,10 ] is efficiently performed. The second injection of endotoxin, on the other hand, leads to massive intravascular formation of fibrin which cannot be removed due to a now severely impaired RES [I I] and, in the rabbit, an ineffective fibrinolytic system [12, 131. It has been shown by others that the concentration of endotoxin used for each injection and the interval between doses are critical in producing the GSR [14,15,161.…”
Section: Speculationmentioning
confidence: 99%
“…When coagulation takes place at a slow rate, the small polymers that are formed do not obstruct the microcirculation and are rapidly cleared by the reticuloendothelial system (18,19). As a result of the intravascular coagulation, the disappearance of labeled fibrinogen from the plasma is accelerated (20): the radioactivity of clottable and nonclottable protein decreases in the plasma in a continuous manner.…”
Section: Discussionmentioning
confidence: 99%